Making Suggestions while Collaborating in L1 English: Common Structures and Strategies - Edstrom, Anne (Miscelánea: A Journal of English and American Studies, 2015)
The present study examines English suggestions that surfaced naturally during a collaborative writing task in a Spanish class. Students’ limited L2 (second language) oral skills made it necessary for them to speak in their L1 (first language), English, while creating a written product in Spanish. Given the interactive nature of the assignment, making suggestions was a collaborative gesture; to remain silent was to be off-task, uncooperative, or uncommitted to the group’s success. This article explores the syntactic structures, pragmatic strategies, and redressive actions used by native speakers of American English when making suggestions. The data indicate that participants made frequent use of modals and did not use the more formulaic strategies included in some lists and taxonomies (Koike 1994; Martínez-Flor 2005)